Clinical features of epilepsy course during COVID-19 - V. A. Mikhailov; N. A. Sivakova; Z. K. Idrisova; N. I. Shova (Эпилепсия и пароксизмальные состояния)
Background. Currently, a great body of data regarding the link between epilepsy and novel coronavirus infection (NCI) has been accumulated. Numerous studies have paid a great attention to rise in frequency and severity of epileptic seizures as well as failure of remission in individuals suffering from epilepsy.Objective: to study clinical and mental changes during NCI in patients with epilepsy.Material and methods. Fifty patients with epilepsy were examined, who were divided into two groups depending on the NCI history: Group 1 (main) – 25 patients undergone COVID-19 in the period from 2020 to 2022; Group 2 (control) – 25 patients not undergone COVID-19 during the same period. Clinical-anamnestic and psychometric methods were used as well as the following scales and questionnaires: National Hospital Seizure Severity Scale (NHS-3), Mini-Mental State Examination (MMSE), Hospital Anxiety and Depression Scale (HADS), Beck Depression Inventory (BDI), Medical Outcomes Study Sleep Scale (MOS-SS), Multidimensional Fatigue Inventory (MFI-20).Results. In patients with epilepsy who had undergone COVID-19, there was a tendency for more frequent epileptic seizures and increased severity of seizure course. Among such patients, mild depression and more severe asthenia, cognitive impairment, moderate sleep disturbances were more common than in the control group.Conclusion. The NCI pandemic has had a pronounced negative impact on the severity of epilepsy (the underlying disease).